Structural, Morphological and Optical Properties of Nanostructured ZrO2 Films Obtained by an Electrochemical Process at Different Deposition Temperatures - Lovchinov, Konstantin; Gergova, Rositsa; Alexieva, Gergana (Coatings, 2022)
This article focuses on the impact of the deposition temperature (in the range from 60 to 80 ◦C) in ZrO2 films obtained by the electrochemical deposition process on SnO2 -covered glass substrates. The solution in which the deposition takes place is aqueous, containing ZrOCl2 with a concentration of 3 × 10−5 M and KCl with a concentration of 0.1 M. By implementing X-ray diffraction (XRD), optical profilometry, scanning electron microscopy (SEM), and UV-VIS-NIR spectroscopy, the temperature dependence of ZrO2 films properties was revealed. The X-ray Diffraction XRD spectra showed six different diffraction maxima ((−111)M, (101)T, (111)M, (112)M, (202)M, and (103)M) associated with the electrochemical ZrO2 layers, and the polycrystalline structure of the films was confirmed at all deposition temperatures. The determination of the average roughness did not indicate significant temperature dependence in the deposited layers. SEM micrographs showed that the layers were composed of grains, most of them of a regular shape, although their size increased slightly with an increased deposition temperature. The coarsest-grained structure was observed for the layers deposited at 80 ◦C. It was demonstrated that the deposition temperature weakly impacts the reflectance and transmittance spectra of the ZrO2 layers. Such layers with low values of specular and high values of diffuse transition, and reflection in the spectral range from 380 to 800 nm, can be applied to various optoelectronic devices such as thin-film solar cells.
Keywords: electrochemical deposition; surface morphology; ZrO2 films; optical measurement; Nigeria; Power; ACE: Sustainable Power and Energy Development; ACE_SPED; University of Nigeria Nsukka